The relation between theory and practice: praxis assumptions for the continuing education of teachers in Early Childhood Education (Práxis Educativa, 2024)
This study aims to discuss some theoretical principles that might underpin the continuing education of teachers working in Early Childhood Education in the praxis perspective. It begins with a review addressing concepts regarding the relation between theory and practice to justify the understanding of praxis as a relevant foundation in teachers’ education processes. The study is based on bibliographical research, guided by the works of Borges and Richter (2021), Freire (1988), Gatti (2020), Martins (2006, 2009), Vázquez (2007), among others. The study indicates that the processes of continuing education for Early Childhood Education teachers require a theoretical-practical conception that enables teachers to engage in a critical and collective enactment, capable of promoting reflection and transformation of educational actions. It also indicates that the specificities of the first stage of Basic Education require training that takes place in context and recognizes educators in their full creative, reflective, and critical potential in their educational action.Keywords: Theory and practice. Teacher’s education. Early Childhood Education. Praxis.